2015
DOI: 10.1080/02755947.2015.1040560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased Discharge on Spawning and Age‐0 Recruitment of Rainbow Trout in the Colorado River at Lees Ferry, Arizona

Abstract: Negative interactions of Rainbow Trout Oncorhynchus mykiss with endangered Humpback Chub Gila cypha pose challenges to the operation of Glen Canyon Dam (GCD) to manage for both species in the Colorado River. Operations to enhance the Rainbow Trout tailwater fishery may lead to an increase in downstream movement of the trout to areas where they are likely to interact with Humpback Chub. We evaluated the effects of dam operations on age‐0 Rainbow Trout in the tailwater fishery to inform managers about how GCD op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The results of our study indicate that these cycles may be avoided by (1) limiting flow conditions that result in large recruitments; (2) decreasing survival rates for young-of-the-year fish during years in which large recruitment events occur by implementing stranding flows; or (3) creating conditions that increase or stabilize prey availability. This study and other studies (Korman et al 2011(Korman et al , 2012Avery et al 2015) have demonstrated that high flows during spring and summer can result in large recruitments, ultimately leading to increases in population size. However, avoiding these flows is difficult owing to the operating rules that govern annual and monthly release volumes from Glen Canyon Dam.…”
Section: Discussionsupporting
confidence: 65%
“…The results of our study indicate that these cycles may be avoided by (1) limiting flow conditions that result in large recruitments; (2) decreasing survival rates for young-of-the-year fish during years in which large recruitment events occur by implementing stranding flows; or (3) creating conditions that increase or stabilize prey availability. This study and other studies (Korman et al 2011(Korman et al , 2012Avery et al 2015) have demonstrated that high flows during spring and summer can result in large recruitments, ultimately leading to increases in population size. However, avoiding these flows is difficult owing to the operating rules that govern annual and monthly release volumes from Glen Canyon Dam.…”
Section: Discussionsupporting
confidence: 65%
“…Second, using flow fluctuations to limit survival rates of recently emerged trout in Glen Canyon (BOR 2011) is a logical alternative as our study indicates that the majority of emigrants from Glen Canyon left within their first year, and possibly within 6 months from emergence. Our results also indicate that the fraction of trout emigrating from Glen Canyon was higher in a year when a large cohort was produced, thus to minimize impacts to the tailwater fishery, flow-control may only be needed in years where large cohorts are anticipated, such as in equalization years (Avery et al 2015) or following controlled floods in spring (Korman et al 2011). Third, it appears that mechanical removal efforts near the LCR will have to be part of any trout control strategy to account for the large population of trout in upper and middle Marble…”
Section: R a F Tmentioning
confidence: 67%
“…Canyon (Avery et al 2015) and increase catch rates in the tailwater fishery (Rogowski et al 2015), unfortunately also lead to higher trout abundance near the LCR. Quantifying the trade-off between the Glen Canyon trout fishery and the status of humpback chub will require continued D r a f t monitoring of both species at the LCR to better define the relationship between rainbow trout abundance and the productivity of the humpback chub population.…”
Section: Discussionmentioning
confidence: 99%
“…In river systems where improvements in water quality are noted, our results suggest positive changes in fish assemblages have occurred over time (e.g., the Illinois and Mississippi rivers); while in river systems where water quality conditions have not improved significantly (e.g., the Tallapoosa River) there is evidence to suggest negative effects (6,22,27). Spatial and temporal changes in Colorado River water temperatures caused by the construction and operation of Glen Canyon Dam and drought ( Fig 2B ) have differentially affected native and non-native fishes [ 31 , 66 , 67 , 68 , 69 , 70 ]. Similarly, the construction of the FCRPS has altered the water temperature regime in the Columbia River and affected native and non-native fishes in different ways [ 71 ].…”
Section: Discussionmentioning
confidence: 99%